2014
DOI: 10.2903/j.efsa.2014.3660
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Dietary Reference Values for iodine

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) derived Dietary Reference Values (DRVs) for iodine, which are provided as Adequate Intake (AI). Iodine is essential for the synthesis of thyroid hormones. Through these hormones, iodine has an important role in energy-yielding metabolism and many other physiological processes. Iodine deficiency is associated with an increased frequency of goitre and hypothyroidism in a population. The AI for iodine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 226 publications
(280 reference statements)
1
77
0
Order By: Relevance
“…Average iodine concentrations of breast milk in Europe have been observed to be around 50-100 µg/L (8-15 µg/100 kcal) (Costeira et al, 2009;EFSA NDA Panel, 2014e).…”
Section: Iodine Content Of Human Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Average iodine concentrations of breast milk in Europe have been observed to be around 50-100 µg/L (8-15 µg/100 kcal) (Costeira et al, 2009;EFSA NDA Panel, 2014e).…”
Section: Iodine Content Of Human Milkmentioning
confidence: 99%
“…In the Panel's previous opinion on nutrient requirements and dietary intakes of infants and young children in the European Union (EFSA NDA Panel, 2013a), the Panel concluded that an iodine intake of 90 µg/day is adequate for the majority of infants. Since there is no reason to assume that infants from birth to six months of age need more iodine than infants in the second half of the first year of life, the Panel considers, in line with its most recent evaluation (EFSA NDA Panel, 2014e), that an intake of iodine of 70 µg/day is adequate for the majority of infants from birth to 12 months of age.…”
Section: Iodine Requirements Of Infantsmentioning
confidence: 99%
“…Iodine is an essential nutrient for mammals, required as a mandatory structural and functional element of thyroid hormones (EFSA NDA Panel, 2014g). Through these hormones, iodine has an important role in energy-yielding metabolism and on the expression of genes that impact many physiological functions, including embryogenesis and growth, and the development of neurological and cognitive functions.…”
Section: Iodinementioning
confidence: 99%
“…Adequate intakes of iodine (200 µg/day) have been estimated for pregnant and lactating women in order to accommodate the increased requirements for iodine (50 µg/day) during pregnancy and lactation (EFSA NDA Panel, 2014). In geographical areas where iodine intakes from other foods are insufficient, seafood consumption during pregnancy may have a major role in the development of the CNS of the foetus.…”
Section: Role Of Nutrients In Seafoodmentioning
confidence: 99%
“…Among the essential nutrients contained in seafood in substantial amounts, DHA and iodine have a wellestablished role in the development of the central nervous system (CNS) of the foetus during pregnancy (EFSA NDA Panel, 2010a, 2014.…”
Section: Role Of Nutrients In Seafoodmentioning
confidence: 99%